IMPLEMENTASI MULTIMEDIA iSPRING DENGAN ANALISIS LEARNING GAP DALAM PEMBELAJARAN DIFERENSIASI DI SEKOLAH DASAR - Badri Atul Fikriyah; Agus Wardhono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In classroom teaching practice, teachers often face complex challenges. One of these challenges is related to the learning gap. One approach that can be applied to address this issue is differentiated learning. However, in its implementation, differentiated learning often faces obstacles, particularly in the aspect of identifying students' specific needs. Given these challenges, there is a need for educational technology innovations that are not only visually appealing but also capable of generating accurate and informative evaluation data, such as through iSpring multimedia. The objective of this study is to describe the implementation of iSpring educational multimedia, equipped with learning gap analysis features, as a supportive tool for differentiated learning in elementary schools. The method employed in this study is descriptive qualitative. The results of this study indicate that iSpring multimedia is highly effective in supporting differentiated learning.